Pelatihan Kader Jumantik dalam Pengendalian Vektor DBD Desa Pandak Kecamatan Baturraden Kabupaten Banyumas - Mela Firdaust; Arif Widyanto; Zaeni Budiono; Sugeng Abdullah; Aris Santjaka; Asep Tata Gunawan; Yulianto (Jurnal Pengabdian Masyarakat - PIMAS, 2025)
The government conducts a program to reduce dengue cases by focusing on preventive. However, the PSN movement launched by the Regent of Banyumas was not optimal. This activity aims to increase the knowledge of jumantik cadres to control of dengue vectors. Pandak Village is a dengue-endemic village. The number of cadres in Pandak Village is 25 peoples, each RT has one jumantik cadre. The implementation of PSN 3M Plus has gone well, but it is not optimal. In its implementation, cadres have not fully understood the larval monitoring instruments that must be filled and how to control them. After the implementation of jumantik cadres training, knowledge of dengue vector control methods increased to 88% which has a very good value category. Cadres have been able to mention breeding places and resting places for dengue vectors. In addition, cadres were also able to mention how to control dengue vectors both physically, biologically and chemically. Each jumantik cadre has understood his duties, namely responsible for monitoring the larval indices together with the household jumantik and recapitulating data per week, and reporting per month to the jumantik coordinator. Periodic reporting of the tiered larval index will ensure the validity of the ABJ data presented in each Health Center. The data is used as a risk assessment of dengue transmission in the work area of the local health center.